(untitled) (Ameghiniana, 2014)
New trilobite species from the San Juan Forrnation, on the west fIank of the Cerro La Silla and Cerro Viejo, near Jáchal (San Juan Province), include late Tremadoc-early Arenig Leiostegium precordilleranus nov. sp., early Arenig Platillaenus niquivilensis nov. sp. and P. jaanussoni nov. sp., late Arenig-early Llanvirn Basilicus (Basiliella) leanzai nov. sp., and Waisfeldaspis beatrizae nov. gen. et sp. A new scutelluine trilobite, Waisfeldaspis nov. gen., is proposed to include a rare species with a pygidium as wide as long, axis very short. and pleural fields with only two pairs of ribs.